Analysis of the Implementation of Electronic Traffic Law Enforcement (ETLE) Tickets Static Directorate Of Traffic, Bengkulu Regional Police: Analisis Implementasi Tilang Electronic Trafic Law Enforcement (ETLE) Statis Direktorat Lalu Lintas Polda Bengkulu - Nur Arifin; Henny Aprianty; Rahiman Dani (Gayaku Publisher, 2026)
This study aims to analyze the implementation of Static Electronic Traffic Law Enforcement (ETLE) at the Traffic Directorate of Bengkulu Regional Police. The study employed a descriptive qualitative approach using the policy implementation theory of Ripley and Franklin, which focuses on compliance, smooth implementation of routine functions, and the achievement of intended performance and impacts. The research informants consisted of personnel from the Traffic Directorate of Bengkulu Regional Police, officers from Bengkulu City Traffic Unit, and members of the public who had received ETLE traffic citations. Data were collected through interviews, observations, and documentation. The findings indicate that the implementation of Static ETLE at the Traffic Directorate of Bengkulu Regional Police has been relatively effective. In terms of compliance, all enforcement procedures have been carried out in accordance with applicable laws, regulations, and Standard Operating Procedures (SOPs). Regarding the smooth implementation of routine functions, the ETLE system has supported continuous traffic monitoring and law enforcement activities, although several challenges remain, including limited camera coverage, internet network disruptions, weather-related recording quality issues, and outdated vehicle ownership data. In terms of performance and intended impacts, ETLE has contributed positively to improving public traffic discipline, enhancing transparency and objectivity in law enforcement, and strengthening police professionalism. However, further improvements are required through infrastructure development, system enhancement, vehicle data updating, and more intensive public socialization programs to optimize ETLE implementation.